2011
DOI: 10.3749/canmin.49.2.417
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Garnet Origins in Granitoid Rocks by Oxygen Isotope Analysis: Examples From the South Mountain Batholith, Nova Scotia

Abstract: Garnet in Nova Scotia's peraluminous South Mountain Batholith (SMB) displays diversity in its texture and composition that has challenged a comprehensive explanation of its origins. In this study, we have employed oxygen isotope analysis to "fingerprint" magmatic, peritectic, and xenocrystic SMB garnets to take advantage of contrasting d 18 O of SMB and metasedimentary country-rocks and the slow rates of diffusion of oxygen in garnet. Among texturally well-characterized garnet, §

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…The presence of garnet in peraluminous granites, including many in the Helgeland Nappe Complex, is commonplace (e.g., Miller and Stoddard, 1981;Allan and Clarke, 1981;Zen, 1988;Erdmann et al, 2009;Lackey et al, 2011). These studies and many others have shown that such garnets are typically almandine rich, as are those studied here.…”
Section: Discussionsupporting
confidence: 60%
“…The presence of garnet in peraluminous granites, including many in the Helgeland Nappe Complex, is commonplace (e.g., Miller and Stoddard, 1981;Allan and Clarke, 1981;Zen, 1988;Erdmann et al, 2009;Lackey et al, 2011). These studies and many others have shown that such garnets are typically almandine rich, as are those studied here.…”
Section: Discussionsupporting
confidence: 60%
“…Van Orman et al (2002) showed that the diffusion rates for Sm and Yb are two to three orders of magnitude slower than those of major elements. Several studies (Spear & Kohn, 1996;Van Orman et al, 2002;Vielzeuf et al, 2005;Villaros et al, 2009a;Lackey et al, 2011a) concluded that because the diffusion coefficients are also small for REE, Zr, Y, O, Ca, and other elements analyzed in this study, growth zoning profiles in phenocrystic garnets would require very long times to homogenize, of the order of tens of millions of years. Hence we consider the trace element profiles observed in the Cardigan Pluton garnet to represent growth zoning profiles.…”
Section: Discussion Diffusion Coefficients For Selected Tracmentioning
confidence: 93%
“…Refractory phases such as garnet and zircon are known to maintain a high degree of inheritance from their sources, even when entrained in granite (e.g., Lackey et al, 2011;Williams, 2001). Table 1 Electron microprobe analyses (wt.%) of experimental granitic melts in equilibrium with common ferromagnesian minerals at 800°C and 200 MPa.…”
Section: Applicationsmentioning
confidence: 99%